Globalization Process and Religion: in the Context of Mutual Relationships - Ganbarov, Asaf (Scholarya Demo Journal of Ruby, 2021)
This article examines the process of globalization and the various aspects of the relationship between religions and globalization on the basis of sociological theories. The study begins with the analysis of the process of globalization, and and demonstrates the effects of globalization on religion that have a variety of implications. First of all, the author argues that world religions are not limited to one nation or region and strive for globalization. Thus, the main messages of world religions are global. Then author claims that the process of globalization has important implications for religion; In the global era, religious pluralism relatively reduces the social importance of religion and accelerates the process of secularization. On the other hand, religion continues to meet the psychological and spiritual needs of people, that is, religion has an individual character and maintains its importance in the modern world. In the end, it is shown that in some cases, religion, acting from a conservative position, plays a barrier to cultural globalization, in other words, Westernization. Thus, religion is the main defender of local cultures, community interests and national identity.